1H NMR-based metabolomic analysis reveals the time-dependent and pH-modulation on the metabolite secretion of Ganoderma boninense and Ganoderma tornatum - Nurazah, Zain; Othman, Abrizah; Sundram, Shamala; Ibrahim, Mohd Hafiz; Mohd Faudzi, Siti Munirah; Ismail, Intan Safinar (Academic Press, 2025)
Ganoderma boninense is a wood-rotting fungus associated with oil palm basal stem rot (BSR) in Malaysia and Indonesia, which causes significant economic losses. Current management strategies have not proven effective in preventing this disease. Moreover, knowledge on the molecular mechanism of the fungus itself is still lacking, as most studies have focused on the host (oil palm). Metabolomics, using nuclear magnetic resonance (NMR) and chemometric analysis, was employed to investigate the metabolite changes in pathogenic G. boninense and non-pathogenic G. tornatum as part of disease management efforts. An in vitro batch culture model was used to grow these fungi at different time points (days 0, 2, 4, 6 and 8) and initial pH adjustment of 4.0, 5.5, 6.0 and 7.0. Methanol-extracted extracellular or secretions of the metabolome were analysed by NMR. Partial least squares-discriminant analysis (PLS-DA) revealed time-dependent metabolic changes modulated by the intracellular pH in both species, with 9 and 8 discriminant metabolites were putatively identified from G. boninense and G. tornatum , respectively. Orthogonal PLS-DA (OPLS-DA) highlighted further species-specific metabolite signatures. Potential key metabolite markers were identified across growth phases: G. boninense showed glucose, xylose and trimethylamine (early phase), and aspartic acid, xylose, betaine, choline and malonic acid (middle-to-late phase). G. tornatum showed arginine, asparagine and lysine (early phase) and xylose, lysine, glucose and trimethylamine (middle-to-late phase). These findings highlight the time-dependent metabolic adaptations influenced by intracellular pH in both fungi. The identification of potential species-specific metabolite signatures across growth phases provides valuable insights into fungal physiology and could help in the early detection and improved management of BSR caused by G. boninense .